Building and Testing of a Conceptual Model to Describe and Measure the Health of People as Affected by Post-traumatic Stress Disorder During Social Unrest: A Confirmatory Factor Analysis and Structural Equation Modeling - Eva Yin-han Chung (Frontiers Media S.A., 2022)
BackgroundSocial unrest affects people's health and well-being. People's health-related needs during social unrest are concerns in both research and clinical practice. This study aimed to build and test a framework to describe and understand the health status and needs of people with post-traumatic stress disorder (PTSD) during social unrest.MethodsThis study was a cross-sectional survey. A total of 460 people who had experienced post-traumatic distress as a result of the social unrest in 2019 and 2020 were included. A conceptual model comprised four essential areas, namely posttraumatic distress symptoms, participation restrictions, perceived stigma and functional disability, was built from literature. Part 1 validated four instruments that evaluate and define the factor structure of these four areas, In Part II, structural equation modeling was used to test and validate a combined model.ResultsFactors underlying the four areas were defined. Analysis using structural equation modeling confirmed a best fit of the model. PTSD symptoms, perceived stigma and participation restriction during social unrest contributed significantly to functional disability; PTSD symptoms exerted a direct effect on participation restriction and perceived stigma; and the effect of PTSD symptoms on functional disability was mediated through its influence on perceived stigma during social unrest.ConclusionsA community-based inclusive approach is essential to understand the holistic needs of people with PTSD during social unrest. To improve health and well-being in addition to evaluating mental health impacts, considering interactions with the rapid change and stressful social environment is essential.